2008
DOI: 10.1051/0004-6361:200809650
|View full text |Cite
|
Sign up to set email alerts
|

Open clusters as key tracers of Galactic chemical evolution

Abstract: Context. Galactic open clusters are since long recognized as one of the best tools for investigating the radial distribution of iron and other metals. Aims. We employed FLAMES at VLT to collect UVES spectra of bright giant stars in a large sample of open clusters, spanning a wide range of Galactocentric distances, ages, and metallicities. We present here the results for four clusters: Berkeley 20 and Berkeley 29, the two most distant clusters in the sample; Collinder 261, the oldest and the one with the minimu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
151
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(173 citation statements)
references
References 73 publications
19
151
2
1
Order By: Relevance
“…It has not been considered further. The mean velocity of the 17 stars classified as members is 19.8 ± 0.9 km s −1 (std error of mean) which agrees well with the values of 20.7 ± 0.6 and 22.1 ± 0.9 km s −1 given by Sestito et al (2008) and Carlberg (2014), respectively. The ten M67 stars observed are all known to be cluster members and the current data support that classification.…”
Section: Melotte 66 and M67 Membershipsupporting
confidence: 85%
See 1 more Smart Citation
“…It has not been considered further. The mean velocity of the 17 stars classified as members is 19.8 ± 0.9 km s −1 (std error of mean) which agrees well with the values of 20.7 ± 0.6 and 22.1 ± 0.9 km s −1 given by Sestito et al (2008) and Carlberg (2014), respectively. The ten M67 stars observed are all known to be cluster members and the current data support that classification.…”
Section: Melotte 66 and M67 Membershipsupporting
confidence: 85%
“…As for the balance of the sample, eight of the nine stars also have velocities and line strengths consistent with membership. The final star is Mel66-W1580 (WEBDA id number), which Sestito et al (2008) indicate is a fast rotator. The radial velocity determined here is 50.9 ± 2.0 km s −1 while that given by Carlberg (2014) is -14 ± 17 km s −1 ; the star is probably a binary.…”
Section: Melotte 66 and M67 Membershipmentioning
confidence: 99%
“…However, not all the investigators have arrived at similar measures of the radial metallicity gradient which may be partly related to the different methods adopted (see for example, Magrini et al 2009;Heiter et al 2014). Our current understanding suggests a gradient of about −0.06 dex kpc −1 (Friel et al 2002;Pancino et al 2010) to −0.20 dex kpc −1 (Frinchaboy et al 2013) in the radial range 5 to 10 kpc with a nearly flat trend (−0.02 dex kpc −1 ) beyond 13 kpc (Carraro et al 2007;Sestito et al 2008;Pancino et al 2010;Yong et al 2012;Frinchaboy et al 2013;Cantat-Gaudin et al 2016).…”
Section: Introductionmentioning
confidence: 70%
“…In recent years, modern high-resolution spectrographs and large reflectors have provided high-quality spectra of stars in OCs for secure measures of abundances, and extended abundance estimates to distant OCs in the direction of Galactic anti-centre (Carraro et al 2007;Yong et al 2005Yong et al , 2012Sestito et al 2006Sestito et al , 2008. However, not all the investigators have arrived at similar measures of the radial metallicity gradient which may be partly related to the different methods adopted (see for example, Magrini et al 2009;Heiter et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, with the advent of high-resolution spectrographs on 8m-class telescopes, it has become possible to derive more secure [Fe/H] estimates, and also to extend metallicity determinations to OCs in the outer disc, beyond 15 kpc from the Galactic centre (Carraro et al 2004;Carretta et al 2004;Yong et al 2005;Sestito et al 2006Sestito et al , 2008. These studies have confirmed the steep slope in the gradient for 7 kpc < R GC < 11 kpc and have shown that the distribution becomes flatter for Galactocentric distances (R GC ) above 11−12 kpc (cf.…”
Section: Introductionmentioning
confidence: 99%